It's not TV : the spectacular rise, revolution, and future of HBO - Gillette, Felix; Koblin, John (Viking, 2022)
"The riveting inside story of HBO, the start-up company that reinvented television-by two veteran media reporters HBO changed how stories could be told on TV. The Sopranos, Sex and the City, The Wire, Game of Thrones. The network's meteoric rise heralded the second golden age of television with serialized shows that examined and reflected American anxieties, fears, and secret passions through complicated characters who were flawed and often unlikable. HBO's own behind-the-scenes story is as complex, compelling, and innovative as the dramas the network created, driven by unorthodox executives who pushed the boundaries of what viewers understood as television at the turn of the century. Originally conceived by a small upstart group of entrepreneurs to bring Hollywood movies into living rooms across America, the scrappy network grew into one of the most influential and respected players in Hollywood. It's Not TV is the deeply reported, definitive story of one of America's most daring and popular cultural institutions, laying bare HBO's growth, dominance, and vulnerability within the capricious media landscape over the past fifty years. Through the visionary executives, showrunners, and producers who shaped HBO, seasoned journalists Gillette and Koblin bring to life a dynamic cast of characters who drove the company's creative innovation in astonishing ways-outmaneuvering copycat competitors, taming Hollywood studios, transforming 1980s comedians and athletes like Chris Rock and Mike Tyson into superstars, and in the late 1990s and 2000s elevating the commercial-free, serialized drama to a revered art form. But in the midst of all its success, HBO was also defined by misbehaving executives, internal power struggles, and a few crucial miscalculations. As data-driven models like Netflix have taken over streaming, HBO's artful, instinctual, and humanistic approach to storytelling is in jeopardy. Taking readers into the boardrooms and behind the camera, It's Not TV tells the surprising, fascinating story of HBO's ascent, its groundbreaking influence on American business, technology, and popular culture, and its increasingly precarious position in the very market it created"--